Preservice primary teachers’ argumentative skills during their participation in a role play on nuclear energy - Cruz-Lorite, Isabel María; Evagorou, Maria; Cebrián-Robles, Daniel; Acebal, María del Carmen (Alicia Benarroch Benarroch, 2022)
This work presents preliminary results of a study on the use of role play on a socioscientific issue for the practice of argumentative skills of preservice primary teachers. The socioscientific issue addressed was the agreement of the Spanish Government and some energy companies for the closure of all Spanish nuclear power plants between 2025 and 2035. The structure and topics of the arguments used during the role-playing discussion were analysed. The results show that the participants use a large amount and variety of evidence and, to a lesser extent, formulate conclusions and justifications. Most of the arguments were on environmental topics, followed by the financial topics and social topics. Finally, the role play seems to be very adequate for the practice of the use of evidence, although the analysis of their quality remains to be done.
Keywords: Profesores - Formación profesional - Congresos; Role play; Argumentation; Socioscientific Issues; Preservice primary teachers; Juego de rol; Argumentación; Problemas sociocientíficos; Profesorado de primaria en formación inicial